Human, social and organizational aspects of health information systems - Kushniruk, Andre W.; Borycki, Elizabeth (Medical Information Science Reference, 2008)
"This book offers an evidence-based management approach to issues associated with the human and social aspects of designing, developing, implementing, and maintaining health information systems across a healthcare organization--specific to an individual, team, organizational, system, and international perspective. Integrating knowledge from multiple levels, will benefit scholars and practitioners from the medical information, health service management, information technology arenas"